Levosimendan Reduces Mortality and Low Cardiac Output Syndrome in Cardiac Surgery - Weber, Carolyn; Esser, Matthias; Eghbalzadeh, Kaveh; Sabashnikov, Anton; Djordjevic, Ilija; Maier, Johanna; Merkle, Julia; Choi, Yeong-Hoon; Madershahian, Navid; Liakopoulos, Oliver; Deppe, Antje Christin; Wahlers, Thorsten C. W. (The Thoracic and Cardiovascular Surgeon, 2020)
Background There has been conflicting evidence concerning the effect of levosimendan on clinical outcomes in patients undergoing cardiac surgery. Therefore, we performed a systematic review and conducted this meta-analysis to provide evidence for/against the administration of levosimendan in cardiac surgery patients.Methods We performed a meta-analysis from literature search in PubMed, EMBASE, and Cochrane Library. Only randomized controlled trials comparing the administration of levosimendan in cardiac surgery patients with a control group (other inotrope, standard therapy/placebo, or an intra-aortic balloon pump) were included. In addition, at least one clinical outcome had to be mentioned: mortality, myocardial infarction, low cardiac output syndrome (LCOS), acute kidney injury, renal replacement therapy, atrial fibrillation, prolonged inotropic support, length of intensive care unit, and hospital stay. The pooled treatment effects (odds ratio [OR], 95% confidence intervals [CI]) were assessed using a fixed or random effects model.Results The literature search retrieved 27 randomized, controlled trials involving a total of 3,198 patients. Levosimendan led to a significant reduction in mortality (OR: 0.67; 95% CI: 0.49–0.91; p = 0.0087). Furthermore, the incidence of LCOS (OR: 0.56, 95% CI: 0.42–0.75; p < 0.0001), acute kidney injury (OR: 0.63; 95% CI: 0.46–0.86; p = 0.0039), and renal replacement therapy (OR: 0.70; 95% CI: 0.50–0.98; p = 0.0332) was significantly decreased in the levosimendan group.Conclusion Our meta-analysis suggests beneficial effects for the prophylactic use of levosimendan in patients with severely impaired left ventricular function undergoing cardiac surgery. The administration of levosimendan was associated with a reduced mortality, less LCOS, and restored adequate organ perfusion reflected in less acute kidney injury.
Keywords: cardiac; coronary artery bypass graft surgery; CABG; heart failure